2017
DOI: 10.1002/2016jb013918
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal distribution of Oklahoma earthquakes: Exploring relationships using a nearest‐neighbor approach

Abstract: Determining the spatiotemporal characteristics of natural and induced seismic events holds the opportunity to gain new insights into why these events occur. Linking the seismicity characteristics with other geologic, geographic, natural, or anthropogenic factors could help to identify the causes and suggest mitigation strategies that reduce the risk associated with such events. The nearest‐neighbor approach utilized in this work represents a practical first step toward identifying statistically correlated clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 27 publications
4
24
0
Order By: Relevance
“…The other mode is located considerably closer in time and space to the origin; it corresponds to clustered events. This bimodality has been documented in multiple regions and on multiple scales (Gentili et al, , ; Gu et al, ; Kossobokov & Nekrasova, ; Moradpour et al, ; Peresan & Gentili, ; Ruhl et al, ; Schoenball et al, ; Trugman et al, ; Vasylkivska & Huerta, ; Zaliapin & Ben‐Zion, , , , ). The bimodality of observed seismicity facilitates cluster detection and declustering.…”
Section: Nearest‐neighbor Proximity For Earthquakesmentioning
confidence: 91%
See 1 more Smart Citation
“…The other mode is located considerably closer in time and space to the origin; it corresponds to clustered events. This bimodality has been documented in multiple regions and on multiple scales (Gentili et al, , ; Gu et al, ; Kossobokov & Nekrasova, ; Moradpour et al, ; Peresan & Gentili, ; Ruhl et al, ; Schoenball et al, ; Trugman et al, ; Vasylkivska & Huerta, ; Zaliapin & Ben‐Zion, , , , ). The bimodality of observed seismicity facilitates cluster detection and declustering.…”
Section: Nearest‐neighbor Proximity For Earthquakesmentioning
confidence: 91%
“…The problem of detecting earthquake clusters (which is different from although closely related to declustering) was shown recently to be effectively addressed by a nearest‐neighbor analysis in space‐time‐magnitude domain (Zaliapin et al, ; Zaliapin and Ben‐Zion, , , , , ). This cluster identification methodology is effective in diverse settings, including tectonic seismicity (Gentili et al, , ; Gu et al, ; Kossobokov & Nekrasova, ; Moradpour et al, ; Peresan & Gentili, ; Reverso et al, ; Ruhl et al, ; Trugman et al, ; Zaliapin et al, ; Zaliapin & Ben‐Zion, , , ), induced earthquakes (Goebel et al, ; Martínez‐Garzón et al, ; Schoenball et al, ; Schoenball & Ellsworth, ; Teng & Baker, ; Vasylkivska & Huerta, ; Zaliapin & Ben‐Zion, ), synthetic seismicity in Epidemic Type Aftershock Sequence (ETAS) models (Gu et al, ; Zaliapin et al, ; Zaliapin & Ben‐Zion, ), and laboratory rock fracture experiments (Davidsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We obtain consistent results as in Figures and S10 using the relocated catalog, suggesting that the influence of relative location differences on spatial decay is insignificant in Oklahoma (Figures S12 and S13). Lastly, we test whether our spatial decay results are sensitive to the choice of cluster identification technique by utilizing the network‐tree algorithm from Zaliapin et al () since it has often been applied in Oklahoma (Vasylkivska & Huerta, ; Zaliapin & Ben‐Zion, ). We use the network‐tree approach as applied in Oklahoma by Goebel et al () to identify clusters and find rapid spatial density decay of aftershocks that is, qualitatively, in close agreement with the results of Figures and S11 (Figures S14–S16).…”
Section: Spatial Aftershock Decaymentioning
confidence: 99%
“…A d f value of 1.6 is used throughout this work as suggested by Zaliapin & Ben-Zion (2013a, 2016a. Zhang & Shearer (2016) tested several variations of this value in Southern California and found that the cluster identification was not greatly affected by alternate choices, though Vasylkivska & Huerta (2017) and Peresan & Gentili (2018) both found that in some areas this could have a significant impact on the binary separation threshold for causally related events.…”
Section: Nearest Neighbour Distancesmentioning
confidence: 99%
“…Events at the same location can be set artificially to a very small spatial separation as in our algorithm, but this will cause a significant stretching of the clustered η j mode, which will then have an affect on the mixture model fit by increasing the length of the tails of the distribution and/or adding a third mode. Though the locations are the most uncertain component of the η j , Vasylkivska & Huerta (2017) suggest that the rescaled spatial distance is critically important in some areas, particularly those which experience induced seismicity. Care should be taken when dealing with small η j events in the catalogue by identifying if the events can reasonably be removed, or if a small perturbation in location should be applied to reposition all events to account for location uncertainty.…”
Section: Issues With Colocated Events and Location Uncertaintymentioning
confidence: 99%